(untitled) (Research, Society and Development, 2021)
Mini-cuttings have been used for several woody species, showing greater efficiency than propagation by conventional cuttings, due to their high yield of propagating material and higher percentage of rooting of mini-cuttings. This work was carried out to evaluate the efficiency of the mini-cutting technique for blackberry ‘Xingu’. The mini-garden was installed in pots from root cuttings. Four mini-cutting collections were carried out from 10/24/2019 to 12/03/2020, that received the following treatments: apical cuttings without IBA, median cuttings without IBA, median cuttings + 500 mg L-1 of IBA and median cuttings + 1000 mg L-1 of IBA. Mini-cutting was performed in a nebulization chamber and evaluated after 35 days. The yield of mini-cuttings increased from the first to the third collection, decreasing in the fourth collection, when the plants started to go into dormancy. The accumulated quantity of blackberry mini-cuttings ’Xingu’ reached 916 m-2, in a period less than 5 months. The percentage of rooted cuttings was generally above 80%, with a significant difference among treatments only in the second collection. The median cuttings showed a greater number and length of roots than the apical ones and the application of IBA had little and varied effect on rooting. It is concluded that the mini-cutting is an efficient technique for the rapid and large-scale propagation of the blackberry ’Xingu’ and can be carried out with all portions of the sprouts of the mini-tumps without the need for auxin.